FENOMENA PENGGUNAAN BAHASA GAUL DI KALANGAN SISWA SD KELAS IV TERHADAP PENGGUNAAN BAHASA INDONESIA - Abilson Ginting; Araida Purba; Muthia Resty; Elly Prihasti Wuriyani; Khairil Anshari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The rapid development of technology and media has had a significant impact on various aspects of society, including the use of good and correct language. Recently, a new trend has emerged among elementary school students, known as slang. Slang Refers to the use of informal language that often contains trendy terms in everyday conversation. Examples of common slang words used include "mantul", "santuy", and others. The use of this slang has triggered concerns in society about its impact on the development of Indonesian among elementary school students. This study aims to analyze the influence of slang on Indonesian, identify commonly used slang vocabulary, analyze the development of slang among lower grade students, and assess the positive and negative impacts of the use of slang. The research method used is a survey delivered to selected respondents, as well as a literature review of relevant books, magazines, and online sources. The novelty of this study lies in the exploration of how slang affects the development of Indonesian among elementary school students.